2017
DOI: 10.1007/s00268-017-4245-7
|View full text |Cite
|
Sign up to set email alerts
|

Open Fracture Management in Low‐Resource Settings: A Medical Training Experience in Cambodian Hospitals

Abstract: This study demonstrates that the capacity building of reconstructive surgery in low-resource settings by local doctors and paramedics is clearly a reasonable option that may substantially reduce amputation of the limbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…804023.17). 4 Testing results showed that the chemical composition of the pins was similar to authentic stainless steel of type SS316/SS316L which is used for medical instruments and fixation screws. The new external fixator frame was accepted and approved by the Secretary of State for Health at the national workshop in Phnom Penh (Cambodia) on June 31, 2011.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…804023.17). 4 Testing results showed that the chemical composition of the pins was similar to authentic stainless steel of type SS316/SS316L which is used for medical instruments and fixation screws. The new external fixator frame was accepted and approved by the Secretary of State for Health at the national workshop in Phnom Penh (Cambodia) on June 31, 2011.…”
Section: Introductionmentioning
confidence: 92%
“…The challenge is therefore to find methods for limb salvage surgery which are feasible in low-resource settings. 4 In most developed countries, larger hospitals typically have multi-disciplinary teams for lower limb reconstruction, including orthopedic surgeons, plastic surgeons, and infectious disease specialists. Those special skills are not available in Cambodian hospitals for the time being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in India reported improved burn management skills, including decreased antibiotic use and earlier excision and grafting [29], while a similar study in Zambia did not report significant changes to burn management protocols or consequent patient outcomes [62]. Carey et al [55] reported on the completion of 93.3% flaps with a 78.1% aversion rate of amputations, while Tajsic et al [13] indicated a 70% primary healing rate of open fractures after orthopedic trauma courses. Participants of the Uganda Sustainable Trauma Orthopedic Program reported a subjective improvement for patients with orthopedic trauma [58].…”
Section: Course Effectivenessmentioning
confidence: 99%
“…The articles in this collection cover a spectrum of topics ranging from specific techniques in the operating room to national policy. These include: details of operative care (fracture care in Cambodia) [1], hospital-wide programs to improve trauma care in Malawi [2], quality improvement (safe surgery checklist in Cambodia) [3], innovative measures to improve access to surgery through use of patient navigators in Haiti [4] and a nationwide surgical plan in Ethiopia [5].…”
mentioning
confidence: 99%